2021
DOI: 10.1038/s41541-021-00307-6
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid nanoparticle encapsulated nucleoside-modified mRNA vaccines elicit polyfunctional HIV-1 antibodies comparable to proteins in nonhuman primates

Abstract: The development of an effective AIDS vaccine remains a challenge. Nucleoside-modified mRNAs formulated in lipid nanoparticles (mRNA-LNP) have proved to be a potent mode of immunization against infectious diseases in preclinical studies, and are being tested for SARS-CoV-2 in humans. A critical question is how mRNA-LNP vaccine immunogenicity compares to that of traditional adjuvanted protein vaccines in primates. Here, we show that mRNA-LNP immunization compared to protein immunization elicits either the same o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 89 publications
0
49
0
Order By: Relevance
“…It remains unknown if the mRNA lipid nanoparticle provides an advantage over conventional adjuvants to generate durable HIV‐1 Env antibody responses as observed for 3M‐052, a TLR‐7/8 agonist [ 123 ] or as cationic LNPs for protein immunogens [ 122 ] — a focus of future studies. The recent success of the mRNA‐based COVID19 vaccines has made this vaccine delivery platform attractive for HIV‐1 vaccines [ 63 , 124 , 125 ]. Moreover, we recently showed that lipid nanoparticle encapsulating mRNA can encode nanoparticles bearing HIV‐1 SOSIP trimers that initiate bnAb precursor B cell lineage expansion in bnAb precursor VH + VL KI mice [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown if the mRNA lipid nanoparticle provides an advantage over conventional adjuvants to generate durable HIV‐1 Env antibody responses as observed for 3M‐052, a TLR‐7/8 agonist [ 123 ] or as cationic LNPs for protein immunogens [ 122 ] — a focus of future studies. The recent success of the mRNA‐based COVID19 vaccines has made this vaccine delivery platform attractive for HIV‐1 vaccines [ 63 , 124 , 125 ]. Moreover, we recently showed that lipid nanoparticle encapsulating mRNA can encode nanoparticles bearing HIV‐1 SOSIP trimers that initiate bnAb precursor B cell lineage expansion in bnAb precursor VH + VL KI mice [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acuitas uses an iterative process correlating biophysical and structural features with potency and safety data to enable the rational design of lipids and LNP compositions with improved potency and therapeutic index [52,53,59,78]. The identification of novel ionizable lipids has enabled several partners and collaborators to investigate the performance of their respective nucleic acid payload [3,28,70,[79][80][81][82][83][84][85][86][87][88][89]. Altogether, these efforts along with others [90][91][92][93][94] to improve the delivery platform have enabled proof-of-concept studies drawing significant success and excitement in several therapeutic applications including protein and enzyme replacement therapy, passive immunization, and prophylactic vaccines, of which several examples will be showcased below.…”
Section: Mrna-lnp Developmentmentioning
confidence: 99%
“…HIV-1 envelope gp160 encoding nucleoside-modified mRNA LNP vaccination induced polyfunctional HIV-1 antibodies at a similar or superior magnitude and breadth compared to adjuvanted protein immunization and durable neutralizing antibodies for 41 weeks in NHPs [134]. Nucleoside-modified mRNA LNP vaccine encoding human cytomegalovirus (HCMV) glycoprotein B (gB) elicited IgG antibodies with more outstanding durability and breadth compared to MF59-adjuvanted gB protein immunization in rabbits [135] and in mice and NHPs [136].…”
Section: Other Viral Mrna Vaccinesmentioning
confidence: 99%